New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Féminisme, art et histoire de l'art - Tucker, Marcia; École nationale supérieure des beaux-arts (France) (Espaces de l'art, 1994)
Ces cinq contributions d'historiennes de l'art et de femmes agissant dans le monde de l'art posent la question des apports du féminisme à l'art récent et au renouvellement de l'histoire de l'art, discipline largement régie, jusqu'au début des années 70, par le regard des hommes. Le féminisme a contribué à renouveler notre conception de l'art. Les auteurs de ce recueil comptent parmi les figures majeures de ce débat.
Keywords: 1900-1999; 1970-1979; 1980-1989; art occidental; arts; cours; discipline; har4600; har4610; histoire de l'art; premier cycle; périodes historiques